Effect of metal thickness on the sensitivity of crack-based sensors - Lee, Eunhan; Kim, Taewi; Suh, Heeseong; Kim, Minho; Pikhitsa, Peter V.; Han, Seungyong; Koh, Je Sung; Kang, Daeshik (Sensors (Switzerland), 2018)
Among many attempts to make a decent human motion detector in various engineering fields, a mechanical crack-based sensor that deliberately generates and uses nano-scale cracks on a metal deposited thin film is gaining attention for its high sensitivity. While the metal layer of the sensor must be responsible for its high performance, its effects have not received much academic interest. In this paper, we studied the relationship between the thickness of the metal layer and the characteristics of the sensor by depositing a few nanometers of chromium (Cr) and gold (Au) on the PET film. We found that the sensitivity of the crack sensor improves/increases under the following conditions: (1) when Au is thin and Cr is thick; and (2) when the ratio of Au is lower than that of Cr, which also increases the transmittance of the sensor, along with its sensitivity. As we only need a small amount of Au to achieve high sensitivity of the sensor, we have suggested more efficient and economical fabrication methods. With this crack-based sensor, we were able to successfully detect finger motions and to distinguish various signs of American Sign Language (ASL).
Keywords: Crack density; Detecting systems; Metal thickness; Sensing systems; Sensitivity; Sensory system; Crack density; Crack-based sensory system; Flexible sensing system; Metal thickness; Motion detecting system; Sensitivity